TRIADODAPHNE, A NEW LAURACEOUS GENUS FROM BORNEO - a. j. g. h. kostermans (Research Center for Biology, 1974)
An illustrated description of the new monotypic genus Triadodaphne myristicoidee is presented, and its similarity to Beilsehmiedia, Crytocarya and Endiandra is discussed.